Screening of 10 DFNB Loci Causing Autosomal Recessive Non-Syndromic Hearing Loss in Two Iranian Populations Negative for GJB2 Mutations - Mahbobeh KOOHIYAN; Somayeh REIISI; Fatemeh AZADEGAN-DEHKORDI; Mansoor SALEHI; Hamidreza ABTAHI; Morteza HASHEMZADEH-CHALESHTORI; Mohammad Reza NOORI-DALOII; Mohammad Amin TABATABAIEFAR (Tehran University of Medical Sciences, 2019)
Background: Autosomal recessive non-syndromic hearing loss (ARNSHL), one of the global public health concerns, is marked by a high degree of genetic heterogeneity. The role of GJB2, as the most common cause of ARNSHL, is only <20% in the Iranian population. Here, we aimed to determine the relative contribution of several apparently most common loci in a cohort of ARNSHL Iranian families that were negative for the GJB2 mutations. Methods: Totally, 80 Iranian ARNSHL families with 3 or more affected individuals from Isfahan and Hamedan provinces, Iran were enrolled in 2017. After excluding mutations in the GJB2 gene via Sanger sequencing, 60 negative samples (30 families from each province) were analyzed using homozygosity mapping for 10 ARNSHL loci. Results: Fourteen families were found to be linked to five different known loci, including DFNB4 (5 families), DFNB2 (3 families), DFNB7/11 (1 family), DFNB9 (2 families) and DFNB3 (3 families). Conclusion: Despite the high heterogeneity of ARNSHL, the genetic causes were determined in 23.5% of the studied families using homozygosity mapping. This data gives an overview of the ARNSHL etiology in the center and west of Iran, used to establish a diagnostic gene panel including most common loci for hearing loss diagnostics.